Relação de variáveis socioeconômicas, contábeis e de controle social com níveis de transparência dos municípios do sul e sudeste do Brasil - Manoel, Geovane Teixeira (2019)
Government transparency is a relevant and notoriously important issue in the accounts of public entities and their component in direct and indirect administrations. Public transparency relates to agency theory and to socioeconomic, accounting and social control variables. Thus, the present study aims to analyze the relationship of socioeconomic, accounting and social control variables with the transparency levels of the municipalities of southeastern and southern Brazil. So, a descriptive research was conducted, seeking to approach the problem quantitatively, selecting 88 municipalities in the southern region and 233 municipalities in the southeastern region evaluated in Brazil’s Transparent Scale in 2018, using analyses with socioeconomic, accounting and accounting variables. Social control through bivariate correlation analysis (Spearman) and comparison of mean in the municipalities of the regions addressed on the study. The results show that, in general, the results of the transparency levels of the municipalities were median, reaching 71% and 68% of the maximum possible score, in the south and southeast regions, respectively, higher than other studies already carried out. In addition, there was a significant and positive correlation between the transparency levels (active and passive) in the sample municipalities in the southeastern region, however, the same scenario was not observed in the southern region. It was also found that, despite the general transparency level of the municipalities that have a Social Observatory of Brazil, they presented higher averages in relation to the transparency level of the ones that do not have the level of general transparency in the municipalities of both regions. Those that had or not the Brazilian Social Observatory, are not statistically different at the 5% significance level. Regarding the relationship of socioeconomic and accounting aspects with the level of general transparency of the municipalities studied, when answering other hypotheses, a positive correlation was found between the level of general transparency and most socioeconomic variables (except Education and Health of municipalities in the southeast region). Confirming the research hypotheses. It was also found that the overall transparency level with the accounting variables Budget Revenue, Union Resource Transfers and the value of Total Assets, showed a positive correlation with all variables of the municipalities of the southeast region, not being observed the same correlation with the variables municipalities in the southern region. Finally, based on the theory chosen and research related to this theme, the possibility that public transparency and better levels of transparency function as a tool to reduce informational asymmetry, increase control and approximate the principal (citizen) and the agent (public manager).